The effects gotu kola (Centella asiatica) powder on growth performance, skin mucus, and serum immunity of Nile tilapia (Oreochromis niloticus) fingerlings - Naphakorn Srichaiyo (2020)
© 2019 The Authors The present study was conducted to assess the possible effects of gotu kola (Centella asiatica) powder (GKP) on skin mucus and serum immune response, as well as growth performance of Nile tilapia, Oreochromis niloticus. Three hundred twenty Nile tilapia fingerlings (average weight of 17.84 ± 0.08 g) were divided into four treatments and fed four levels of gotu kola powder (GKP) as following 0, 5, 10, and 20 g kg−1 diet for 61 days. Completed Randomised Design with four replications was applied. The results showed that fish fed 5 g kg−1 GKP significantly improved skin mucus lysozyme (SMLA) and skin mucus peroxidase activities (SMPA) (P < 0.05). However, no significant differences in SMLA and SMPA were observed in fish fed 10 and 20 g kg−1 GKP compared to the control group (P > 0.05). For serum immunity, dietary administration of GKP showed significantly improved serum lysozyme and serum peroxidase activities compared to control group (P < 0.05). The highest value was found in fish fed 5 and 10 g kg−1 GKP (P < 0.05). Similarly, a significant increase in alternative complement (ACH50), phagocytosis, and respiratory burst activities were recorded in fish fed 5 and 10 g kg−1 GKP compared to the control (P < 0.05). However, no significance was observed in fish fed 20 g kg−1 GKP compared to the control. Similarly, no significant difference in growth performance, feed conversion ratio, and survival rate was observed in fish fed GKP compared to the control. In summary, diets supplemented with GKP (10 g kg−1) increased serum and mucosal immunity. However, GKP supplementations had no effects on Nile tilapia growth and survival rate.